2020
DOI: 10.3390/biom10030405
|View full text |Cite
|
Sign up to set email alerts
|

PMCA Applications for Prion Detection in Peripheral Tissues of Patients with Variant Creutzfeldt-Jakob Disease

Abstract: Prion diseases are neurodegenerative and invariably fatal conditions that affect humans and animals. In particular, Creutzfeldt-Jakob disease (CJD) and bovine spongiform encephalopathy (BSE) are paradigmatic forms of human and animal prion diseases, respectively. Human exposure to BSE through contaminated food caused the appearance of the new variant form of CJD (vCJD). These diseases are caused by an abnormal prion protein named PrPSc (or prion), which accumulates in the brain and leads to the onset of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…Here we examined the ability of CAC-717 to inactivate prion proteins. Western blotting was used for PrP Sc analysis, and protein misfolding cyclic amplification (PMCA), which mimics the in vivo reaction and amplifies PrP Sc in vitro [28][29][30], was used to examine the seeding activity of PrP Sc . In both assays, PK-resistant PrP (PrPres) was used as an indicator of PrP Sc .…”
Section: Introductionmentioning
confidence: 99%
“…Here we examined the ability of CAC-717 to inactivate prion proteins. Western blotting was used for PrP Sc analysis, and protein misfolding cyclic amplification (PMCA), which mimics the in vivo reaction and amplifies PrP Sc in vitro [28][29][30], was used to examine the seeding activity of PrP Sc . In both assays, PK-resistant PrP (PrPres) was used as an indicator of PrP Sc .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated prion pathogenesis and neurotoxic pathways in vivo using Rocky Mountain Laboratory (RML) infection and antibody-derived anti-PrP ligands ( 61 63 ). In these studies, the neurodegenerative changes typical of prion diseases were observed without detectable PrPsc, suggesting the presence of additional mechanisms of neuronal death in prion disorders, aside from those related to PrPsc ( 64 , 65 ). We suggest that prion peptide may have valuable role as a therapeutic strategy for prion diseases though PrP (106–126) is not equivalent to PrPsc.…”
Section: Discussionmentioning
confidence: 77%
“…Previous literature has investigated prion pathogenesis and neurotoxic pathways using Rocky Mountain Laboratory (RML) strain and antibody-derived anti-PrP ligands in in vivo models [51][52][53]. Typical neurodegenerative fluctuations in prion diseases have been observed in the absence of detectable PrPsc, suggesting that prion disorders are caused by alternative mechanisms of neuronal damage, as well as PrPsc [54,55]. PrP 106-126 has been suggested as one such alternative contributor to the pathogenic and molecular properties of PrPsc [56].…”
Section: Discussionmentioning
confidence: 99%